Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Kemampuan Pemahaman Konsep Peserta Didik Pada Materi Himpunan Di Kelas VII C SMP Negeri 2 Bandar Laksamana - Raudah Harahap (Departement of Mathematics Education, 2021)
This study aims to determine the ability to understand mathematical concepts in students with the Problem Based Learning (PBL) model on the set material. The subjects in this study were students of class VII C of SMP Negeri 2 Bandar Laksamana. The object of this research is the Problem Based Learning model to improve students' understanding of mathematical concepts with set material. The data analysis technique in this study is Classroom Action Research, which is to determine the ability to understand the concepts of students by using the Problem Based Learning (PBL) model. Data collection techniques and tools in this study were through tests and observations carried out during mathematics learning activities. The data on the initial test of students' learning mastery levels are written in the form of tables and graphs. In the initial test, the students' learning mastery level classically obtained 12 students (44%) who completed 15 students (56%) who did not complete. In the first cycle there was an increase, namely 16 students (59%) who completed, while 11 students (41%) had not completed, and in the second cycle there was an increase again to 22 students (85%) who completed, the results of observations the students who were conducted by the researchers showed an average result in the first cycle of 72.07 and in the second cycle of 84.18. Students' mathematics learning activities have increased starting from the initial test, cycle I, and cycle II. So it can be concluded that learning using the Problem Based Learning (PBL) model can improve students' conceptual understanding of the set material in class VII C of SMP Negeri 2 Bandar Laksamana.